Digitation associated with defecation: what does it mean in urogynaecological patients?. Issue 2 (February 2016) - Hai-Ying, Cao; Rojas, Rodrigo; Hall, Jessica; Atan, Ixora; Dietz, Hans
Abstract Introduction and hypothesis Obstructed defecation is a common symptom complex in urogynaecological patients, and perineal, vaginal and/or anal digitation may required for defecation. Translabial ultrasound can be used to assess anorectal anatomy, similar to defecation proctography. The aim of the present study was to determine the association between different forms of digitation (vaginal, perineal and anal) and abnormal posterior compartment anatomy. Methods A total of 271 patients were analysed in a retrospective study utilising archived ultrasound volume datasets. Symptoms of obstructed defecation (straining at stool, incomplete bowel emptying, perineal, vaginal and anal digitation) were ascertained on interview. Postprocessing of stored 3D/4D translabial ultrasound datasets obtained on maximal Valsalva was used to diagnose descent of the rectal ampulla, rectocoele, enterocoele and rectal intussusception at a later date, blinded to all clinical data. Results Digitation was reported by 39 % of our population. The position of the rectal ampulla on Valsalva was associated with perineal (p  = 0.02) and vaginal (p  = 0.02) digitation. The presence of a true rectocoele was significantly associated with perineal (p  = 0.04) and anal (p  = 0.03) digitation. Rectocoele depth was associated with all three forms of digitation (P  = 0.005–0.02). The bother of symptoms of obstructed defecation was strongly associated with digitation (allP  < = 0.001), with no appreciable difference in bother among the three forms. Conclusion Digitation is common, and all forms of digitation are associated with abnormal posterior compartment anatomy. It may not be necessary to distinguish between different forms of digitation in clinical practice.